2016
DOI: 10.1021/acs.joc.6b00416
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Comprehensive Structural and Chiroptical Characterization of Enones Derived from (−)-α-Santonin by Experiment and Theory

Abstract: The aim of the present work is to explain the causes of the observed deviations from sector and helicity rules to determine the absolute configuration of optically active α,β-unsaturated ketones by means of electronic circular dichroism (ECD). To this end, a series of model compounds with a common decahydronaphthalene skeleton representing both cisoid and transoid enones were synthesized. In the framework of this work, detailed dichroic studies supported by single crystal X-ray analysis were performed where po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 67 publications
2
11
0
Order By: Relevance
“…39,40 This also holds true in the case of the studied molecule. Comparison of the ECD spectra of individual conformers shows that there is no characteristic band (with the unchanged position and sign), which could be used for the C17 center configuration assignment (Figs.…”
Section: Resultssupporting
confidence: 70%
“…39,40 This also holds true in the case of the studied molecule. Comparison of the ECD spectra of individual conformers shows that there is no characteristic band (with the unchanged position and sign), which could be used for the C17 center configuration assignment (Figs.…”
Section: Resultssupporting
confidence: 70%
“…The NOE interaction between H 3 -12 (δ H 1.24, d, J = 6.8 Hz) and H-2 reflected both H-2 and H-4 in a trans orientation. Based on the enone helicity rule, 22 the negative Cotton effect (CE) at 340 nm and the positive CE at 250 nm were attributed to n → π* and π → π* transitions of the enone chromophore (Figure 3c) for an M-type enone torsion angle, implying the existence of the 2S configuration. This assignment was in agreement with the computed ECD data for a model molecule without methyl substitution at C-4 but with (2S)-OH (Figure S86l.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This data suggested that both H-2 and H-4 were on the same face, differing from 3 . According to the enone helicity rule, the positive CE at 340 nm and negative CE at 250 nm for n → π* and π → π* transitions in 4 (Figure d) agreed with a P -type helicity of the enone torsion angle, suggesting the existence of the 2 R configuration. The Mitsunobu reaction allowed the conversion of 4 to 3 , supporting 4 as the 2-epimer of 3 .…”
Section: Results and Discussionmentioning
confidence: 99%
“…Previous studies have shown that for some optical properties, MD sampling is essential 29,40,44,167–169 . Here, an MD simulation is performed, and snapshots are taken equidistantly from the resulting trajectory.…”
Section: Example Applications and Benchmarkingmentioning
confidence: 99%